Tectono-Stratigraphic Model of East Face of Central Gunung Semanggol, Bukit Merah, Taiping, Perak - Bin Mohd Mazlan, Muhammad Radziamir (Universiti Teknologi PETRONAS, 2016)
The purpose of this study is to use the data recorded during the research is to understand depositional settings, structures of Gunung Semanggol and finally, develop a tectono-stratigraphic model. Different methods were done in collecting data across three different geological outcrops along the east face of the central Gunung Semanggol such as the sedimentary logs and strike and dip measurements. Structural complexities including faults, folds and fractures in the three outcrops were observed and interpreted in the structural analysis which are valuable in interpretation and understanding the connection between outcrops of the Semanggol Formation.